(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the outcome in terms of delivery within 24 hours of induction of labour of immediate induction versus delayed induction of labour in term Pre-labour rupture of membrane. Study Design: Randomized controlled trial Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology, Civil Hospital, Bahawalpur from November 2018 to April 2019. Materials and Methods: 154women at term (gestational age ≥37 weeks) were enrolled. All with premature rupture of membrane, & of between 18-40 years of age. They were divided in 2 equal batches (A&B). Patients with multiple pregnancy, fetal weight more than 4 kgs, uncontrolled diabetes mellitus and h/o uterine surgery were excluded. Labour induction was carried out after 6 hours and after 24 hours of presentation in group A and B patients respectively. Outcome was measured in both groups in term of delivery within 24 hours of induction of labour. Results: The average age of participants in batch A was 27.77 ± 3.14 years and in batch B was 28.09 ± 3.38 years. The mean found for gestational age was 39.01 ± 1.31 weeks. The mean parity in batch A& batch B was 2. Satisfactory outcome in batch A (immediate induction) was seen in 68 (88.31%) while in Group B (delayed induction) was seen in 54 (70.13%) patients (p-value = 0.005). Conclusion: This study concluded that outcome of immediate induction is better as compared to delayed induction in term, pre-labour rupture of membrane (PROM).